2014
DOI: 10.1016/j.jvs.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Open versus endoscopic great saphenous vein harvest for lower extremity revascularization of critical limb ischemia

Abstract: OVH and EVH have similar failure mechanisms, limb salvage, amputation-free survival, and overall survival. EVH is associated with impaired patency, increased need for intervention, longer operative times, shorter hospital stays, and decreased vein harvest site wound complications. OVH of the great saphenous vein may provide optimal patency but was not necessarily associated with better patient-centered outcomes. Similar limb salvage rates and amputation-free survival may justify the use of EVH, despite inferio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
5
28
1
1
Order By: Relevance
“…Although our overall wound complication rate of 43% in the OVH group seems high, it includes all complications including Szilagyi I, and it is not too dissimilar from the previous reported rates in series from single academic centers (23%-44%). 10,11,15,19 Our study also found that both BMI and prior surgery were independently associated with wound complications. The relationship between increased BMI and surgical wound complications has been demonstrated in several previous studies.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Although our overall wound complication rate of 43% in the OVH group seems high, it includes all complications including Szilagyi I, and it is not too dissimilar from the previous reported rates in series from single academic centers (23%-44%). 10,11,15,19 Our study also found that both BMI and prior surgery were independently associated with wound complications. The relationship between increased BMI and surgical wound complications has been demonstrated in several previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…One of the concerns is inferior patency and increased rates of reinterventions associated with EVH. [10][11][12][13][14]16 Our study shows that in experienced hands, EVH is associated with similar graft patency, reintervention rates, and limb salvage and fewer harvest site complications.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Handling of the surgically harvested vein is a strong outcome determinant (Conte 2009;Santo et al 2013). Preimplantation histological analysis has been proposed (Giannoukas et al 1997).…”
Section: Introductionmentioning
confidence: 99%